2021
DOI: 10.1002/bab.2150
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive review on anticancer mechanism of bazedoxifene

Abstract: Cancer is counted as a second leading cause of death among nontransmissible diseases. Identification of novel anticancer drugs is therefore necessary for the effective treatment of cancer. Conventional drug discovery is time consuming and expensive process. Unlike conventional drug discovery, drug repositioning offers a novel strategy for urgent drug discovery since it is a cost-effective and faster process. Bazedoxifene (BZA) is a synthetic selective estrogen receptor modulator, approved by the United States … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 203 publications
(418 reference statements)
0
8
0
Order By: Relevance
“…Bazedoxifene (Duavive ® ) is a synthetic SERM, which received approval by the United States Food and Drug Administration for the treatment of osteoporosis in postmenopausal women. It is now being studied as a repositioned drug for its anticancer activity in different types of cancers including BC [ 58 ]. Recently, the combination of BZA and palbociclib showed clinical efficacy and an acceptable safety profile in a heavily pretreated patient population with advanced HR + /HER2 − BC [ 59 ].…”
Section: Breast Cancer Therapiesmentioning
confidence: 99%
“…Bazedoxifene (Duavive ® ) is a synthetic SERM, which received approval by the United States Food and Drug Administration for the treatment of osteoporosis in postmenopausal women. It is now being studied as a repositioned drug for its anticancer activity in different types of cancers including BC [ 58 ]. Recently, the combination of BZA and palbociclib showed clinical efficacy and an acceptable safety profile in a heavily pretreated patient population with advanced HR + /HER2 − BC [ 59 ].…”
Section: Breast Cancer Therapiesmentioning
confidence: 99%
“…Recent studies have shown that bazedoxifene has potent anticancer activity in several types of cancer [30,44] . These properties, which are now being studied both in vitro and in vivo, make bazedoxifene a promising anticancer drug.…”
Section: Treatment Of Pmopmentioning
confidence: 99%
“…4 The reason behind increasing cases is complex and reflects aging, population growth, and inefficient treatment along with prevalence and distribution of main risk factors of cancer, most of which are associated with socioeconomic development. 2 Chemotherapy, radiation therapy, hormone therapy, immune therapy, targeted therapy, surgery, and laser therapy are currently being used in cancer treatment. 5,6 Despite these advancements, the promising option for cancer treatment is chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…Its global burden is expected to be 28.4 million cases in 2040 4 . The reason behind increasing cases is complex and reflects aging, population growth, and inefficient treatment along with prevalence and distribution of main risk factors of cancer, most of which are associated with socioeconomic development 2 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation